Mediasi komitmen organisasi pada kompetensi kerja dan motivasi kerja dalam meningkatkan kinerja tenaga penyuluh - Erma Suriadarma; Agus David Ramdansyah; Liza Mumtazah Damarwulan (Amal Insani Foundation, 2023)
This study aims to examine the effect of competence and work motivation in improving the performance of extension workers through organizational commitment as an mediation variable. The object of this research is the Field Cooperative Extension Officer of the Banten Province Cooperatives and SMEs Office. The population in this study was 50 people, while the sampling used a survey technique or saturated sample, which means that the entire population was sampled. The results of this study indicate that competence directly has a significant impact on the performance of extension workers but does not have a significant impact on organizational commitment. Furthermore, work motivation has a significant effect on the performance of the extension workers and organizational commitment, while organizational commitment has a significant impact on the performance of the extension workers. On the other hand, organizational commitment can mediate between work motivation and performance of extension workers but cannot mediate on the competence and performance of extension workers.